Hubungan Asupan Makanan dengan Status Gizi Anak SD Swasta Karya Bakti Kota Medan - Purba, Tuty Hertati; Anggoro, Sarni; Rachmawati, Nisya Ayu; Lestari, Wanda; Dongoran, Alifia Salsabila; Wijaya, Gali; Harefa, Maslena; Utami, Silfi Dwi; Kemala, Sintia Anggi; Harahap, Usni Anriani (Media Gizi Ilmiah Indonesia, 2024)
School-aged children are considered the nation’s investment as they are the successors of the nation. According to the Nutritional Status Monitoring (PSG) report from the Health Office of North Sumatra Province in 2022, 8.8% of children aged 5-12 years are classified as very underweight and underweight based on BMI-for-age. This study aims to examine the relationship between food intake and nutritional status of elementary school children at Karya Bakti Private School in Medan. The research uses a quantitative survey design with a cross-sectional approach. The population consists of all 5th-grade students at Karya Bakti Private School in Medan, totaling 26 samples. Data analysis was conducted using univariate and bivariate analysis with the chi-square test. The results from the 26 samples showed that 15.4% of those with inadequate food intake had poor nutritional status, 46.1% with inadequate food intake had normal nutritional status, 19.2% with adequate food intake had normal nutritional status, 15.4% with excessive food intake had excessive nutritional status, and 3.8% with excessive food intake were obese. The chi-square test yielded a p-value of 0.01, indicating that food intake is related to nutritional status. On the basis of the obtained data, we conclude that there is a relationship between food intake and nutritional status among elementary school children at Karya Bakti  School in Medan.